Optimal Sticky Prices Under Rational Inattention - Bartosz Maćkowiak; Mirko Wiederholt (Credit and Capital Markets – Kredit und Kapital, 2019)
This paper presents a model in which price setting firms decide what to pay attention to, subject to a constraint on information flow. When idiosyncratic conditions are more variable or more important than aggregate conditions, firms pay more attention to idiosyncratic conditions than to aggregate conditions. When we calibrate the model to match the large average absolute size of price changes observed in micro data, prices react fast and by large amounts to idiosyncratic shocks, but only slowly and by small amounts to nominal shocks. Nominal shocks have strong and persistent real effects. An optimizing trader will process those prices of most importance to his decision problem most frequently and carefully, those of less importance less so, and most prices not at all. Of the many sources of risk of importance to him, the business cycle and aggregate behavior generally is, for most agents, of no special importance, and there is no reason for traders to specialize their own information systems for diagnosing general movements correctly. – Robert E. Lucas (1977, 21)
Keywords: D21; D83; E31; E52; 330; Rational Inattention: Sticky Prices; Real Effects of Nominal Shocks